The a to Z of British Intelligence - West, Nigel (Rowman & Littlefield Publishers, 2009)
The A to Z of British Intelligence offers insight into the history and operations of British Intelligence through its more than 1,800 entries, covering a vast and varied cast of characters: the spies and their handlers, the moles and defectors, the political leaders, the top brass, the techniques and jargon, and the many different offices and organizations. Covered also are the agencies; leading individuals and prominent personalities; operations, including double agent and deception campaigns; and events, using the most up-to-date declassified material, but written in a style for the professional and general reader alike. This text features 16 black-and-white photographs, an extensive chronology, and a comprehensive bibliography.